Clinical effects of glabellar botulinum toxin injections on borderline personality disorder: A randomized controlled trial. (February 2022) - Wollmer, M Axel; Neumann, Insa; Jung, Stefanie; Bechinie, Agnès; Herrmann, Julian; Müller, Antje; Wohlmuth, Peter; Fournier-Kaiser, Larissa; Sperling, Christian; Peters, Liza; Kneer, Jonas; Engel, Jannis; et al.
Background: Inhibition of frowning via injections of botulinum toxin A (BTX) into the glabellar region has shown beneficial effects in the treatment of major depression. Preliminary research suggests that improvements in the affective domain are not depression-specific, but may also translate to other psychiatric disorders. Aim: This 16-week, single-blind, two-center randomized controlled trial investigated the influence of BTX on clinical symptoms of borderline personality disorder (BPD). Methods: Fifty-four patients with BPD were randomly assigned to treatment with BTX (n  = 27) or a minimal acupuncture (ACU) control condition ( n  = 27). Clinical outcomes were followed at 2, 4, 6, 8, 12, and 16 weeks. Primary endpoint was the relative score change on the Zanarini Rating Scale for Borderline Personality Disorder (ZAN-BPD) 8 weeks after baseline relative to the control group and adjusted for treatment center. Secondary and additional outcome variables were self-rated borderline symptoms, comorbid symptoms of depression, psychological distress, and clinical global impression. Results: Participants showed significant improvements at the primary efficacy endpoint in both treatment groups (BTX: M  = −0.39, SD  = 0.39; ACU: M  = −0.35, SD  = 0.42), but no superior effect of the BTX condition in comparison with the control intervention was found— F (1, 5323) = 0.017, p  = 0.68). None of the secondary or additional outcomes yielded significant group differences. Side effects were mild and included headache, transient skin or muscle irritations, and dizziness. Conclusion: Evidence regarding the efficacy of BTX for BDP remains limited, and the design of adequate control conditions presents an opportunity for further research. ClinicalTrials.gov registry : Botulinum Toxin A for Emotional Stabilization in Borderline Personality Disorder (BPD), NCT02728778, https://clinicaltrials.gov/ct2/show/NCT02728778